Electrospun composite nanofiber membrane, preparation method and application

The preparation of sandwich-structure composite nanofiber membranes through electrospinning has solved the problems of environmental pollution, waste of raw materials and inconsistent with the skin of traditional facial masks, and the integration of the facial mask and essence is achieved, with good mechanical properties and biocompatibility.

CN116077350BActive Publication Date: 2025-04-18SHANDONG FREDA BIOTECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211120744.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-15
Publication Date
2025-04-18
Estimated Expiration
2042-09-15

AI Technical Summary

Technical Problem

Traditional facial masks have problems such as environmental pollution, waste of raw materials, complex process, and inconsistent masks with skin, and chemical additives damage to the skin.

Method used

The sandwich structure composite nanofiber membrane was prepared by electrospinning method. The membrane cloth was composed of a biocompatible electrospun polyvinyl alcohol/sodium hyaluronate nanofiber membrane, a functional layer containing chitosan, hyaluronate and its derivatives, collagen peptides, and an ultra-thin thermoplastic polyurethane nanofiber membrane.

Benefits of technology

It solves the problem of difficult recycling of the protective layer and functional layer of the mask, achieves a good fit between the mask and the skin, avoids the damage of chemical additives to the skin, and has high breathability, flexibility and excellent mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116077350B_ABST
    Figure CN116077350B_ABST
Patent Text Reader

Abstract

The present invention discloses an electrospun composite nanofiber membrane, a preparation method and an application. The present invention uses an electrospinning method to successfully prepare a sandwich structure composite fiber membrane of an adhesion layer (biocompatible electrospun polyvinyl alcohol / sodium hyaluronate nanofiber membrane), a functional layer (nanofiber membrane containing chitosan, hyaluronate and its derivatives, and collagen peptides) and a flexible breathable layer (ultra-thin thermoplastic polyurethane nanofiber membrane). The membrane cloth has good flexibility, hydrophilicity, water swelling performance and mechanical properties, which solves the problems of the difficulty in recycling the protective layer and functional layer of traditional facial masks, resulting in waste of resources, environmental pollution and poor fit with the skin. At the same time, the membrane cloth is no longer just a carrier, but can dissolve by itself to play the role of essence, successfully realizing the integration of the mask cloth and the essence, and solving the problem of chemical additives damaging the skin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of facial masks and relates to an electrospun composite nanofiber membrane, a preparation method and an application thereof. Background Art

[0002] As a new generation of consumers gradually occupy the mainstream of consumption, the use of facial masks is becoming more and more popular and daily. The existing preparation methods of facial mask cloth include sizing, spunlace, physical or chemical bonding. Among them, the sizing method is cumbersome to operate and is not suitable for mass production; the spunlace process equipment is complex and the production cost is high; the physical or chemical bonding method requires bonding reinforcement. In addition, traditional facial masks contain chemical preservatives and various flavors that are not friendly to the skin. The protective layer and functional layer of the mask are difficult to recycle, which can easily cause waste of resources and environmental pollution. In addition, the poor mechanics and flexibility of traditional facial masks indirectly lead to the poor fit of most traditional facial masks to the skin. Therefore, it is urgent to develop new facial masks to solve the problems of environmental pollution, waste of raw materials, complex processes, poor fit between the mask and the skin, and chemical additives that damage the skin caused by traditional facial masks.

[0003] Electrospinning technology is currently one of the most important methods for preparing continuous nanofibers. Electrospinning is a technology that uses polymer solutions or melts to perform jet spinning under a strong electric field to produce nanoscale continuous fibers. The process has the advantages of simple equipment, low cost, easy control of fiber morphology, and large-scale production. The nanoscale fiber membrane prepared by this process has the advantages of large specific surface area, high porosity, and large active ingredient loading. The electrospun nanofiber membrane has good flexibility, air permeability, and excellent mechanical properties, and has great potential for application in facial masks. Summary of the invention

[0004] In view of the above problems existing in traditional facial masks, the present invention provides an electrospun composite nanofiber membrane, a preparation method and application. The present invention successfully prepares a sandwich structure composite fiber membrane by electrospinning. The membrane cloth has good flexibility, hydrophilicity, water swelling performance and mechanical properties, which solves the problems of the difficulty in recycling the protective layer and functional layer of traditional facial masks, resulting in waste of resources, environmental pollution and poor fit with the skin. At the same time, the membrane cloth is no longer just a carrier, but can dissolve by itself to play the role of essence, successfully realizing the integration of mask cloth and essence, and solving the problem of chemical additives damaging the skin.

[0005] The technical solution of the present invention is: an electrospun composite nanofiber membrane, characterized in that it is a sandwich structure composite nanofiber membrane consisting of an adhesive layer (in direct contact with the skin), a functional layer and a flexible breathable layer;

[0006] The adhesive layer is a biocompatible electrospun polyvinyl alcohol / sodium hyaluronate nanofiber membrane; the mass ratio of polyvinyl alcohol to sodium hyaluronate is 90:10-50:50;

[0007] The functional layer is a nanofiber membrane comprising chitosan, hyaluronate and its derivatives, and collagen peptide; the mass ratio of chitosan, hyaluronate and its derivatives, and collagen peptide is 1:0.8-1.2:0.5-2;

[0008] The flexible breathable layer is an ultra-thin thermoplastic polyurethane nanofiber membrane.

[0009] The method for preparing the sandwich structure composite nanofiber membrane comprises the following steps:

[0010] 1) Preparation of Adhesion Layer

[0011] Take polyvinyl alcohol and sodium hyaluronate, add water, heat and stir respectively to obtain two spinning solutions; transfer the spinning solutions into syringes respectively, fix the syringes on a high-voltage electrospinning instrument, set the receiving device to pattern, and electrospin in coaxial electrospinning mode, with the inner layer being sodium hyaluronate and the outer layer being polyvinyl alcohol, and the electrospinning film thickness is 20 to 30 μm, and the first layer of patterned nanofiber film;

[0012] 2) Preparation of functional layer

[0013] Dissolve chitosan, hyaluronate and its derivatives, and collagen peptide in water to form a spinning solution, and mix them in an electrospinning mode to directly receive the functional layer nanofiber membrane on the adhesive layer prepared in step 1), with a membrane thickness of 60 to 80 μm;

[0014] 3) Preparation of flexible breathable layer

[0015] Thermoplastic polyurethane is weighed and dissolved in N,N-dimethylformamide (DMF) solvent to obtain a spinning solution, and a flexible breathable layer nanofiber membrane is directly received on the functional layer in step 2), and the membrane thickness is 8 to 12 μm.

[0016] Preferably, the concentrations of the polyvinyl alcohol and sodium hyaluronate spinning solutions in step 1) are 8-10wt% and 5-10wt% respectively. During the spinning process, the relative humidity (RH) of the air is 25-40%, the temperature is room temperature, and the receiving distance is 7 cm.

[0017] Preferably, in the above step 2), the mass percentage of the functional layer and distilled water is 8-12%; during the spinning process, the relative humidity (RH) of the air is 30-40%, the temperature is room temperature, and the receiving distance is 10 cm.

[0018] Preferably, the concentration of the thermoplastic polyurethane spinning solution in step 3) is 0.1-0.15 g / ml, the relative humidity (RH) of the air during the spinning process is 30-40%, the temperature is room temperature, and the receiving distance is 8 cm.

[0019] The adhesive layer of the present invention is composed of a biocompatible electrospun polyvinyl alcohol / sodium hyaluronate nanofiber membrane, wherein the polyvinyl alcohol has good hydrophilicity and enhances adhesion to the skin. The first layer of hyaluronic acid has the effect of repairing and retaining moisture on the skin, gradually forming a layer of water-rich film, while transporting moisture inward and outward to prevent the skin from being too dry.

[0020] The functional layer of the present invention comprises chitosan, hyaluronate and its derivatives, and collagen peptides, wherein chitosan has antibacterial properties and can prevent bacterial erosion; hyaluronate and its derivatives have strong moisturizing, repairing and anti-aging effects; they can maintain the metabolic balance of skin cells and enhance the skin barrier, and are ideal tissue engineering scaffold materials, wound repair materials, etc. Collagen peptides are obtained by hydrolysis of collagen and are an ideal source of supplementary collagen for the human body. They can increase cell activity, maintain the skin's moisturizing and hydrating ability, and improve skin glossiness.

[0021] Regarding the functional layer, hyaluronic acid is a water-soluble natural polyelectrolyte polymer. However, it is very difficult to electrospin hyaluronic acid nanofibers directly. This is mainly due to the following two reasons: 1. There is not enough chain entanglement between hyaluronic acid molecules, and droplets are prone to appear during the electrospinning process. 2. There are a large number of hydroxyl groups in the single helical molecular chain of hyaluronic acid, which form hydrogen bonds with water molecules and lock them in their single helical structure, forming droplets during the electrostatic spinning process. During the electrostatic spinning process of the present invention, the electric field induces phase separation of polyelectrolytes, wherein the polycations move along the direction of the electric field lines, and the polyanions move in the opposite direction of the electric field lines. By destroying the single helical structure of hyaluronic acid, the chain entanglement between molecules is increased, the surface tension of the spinning solution is reduced, the liquid volatilization rate is enhanced, and polymers (chitosan, collagen peptides) are added to improve the spinnability of hyaluronic acid.

[0022] The thermoplastic polyurethane of the flexible breathable layer, as a hydrophobic polymer with excellent mechanical properties, can improve the mechanical properties.

[0023] The composite nanofiber membrane prepared based on the above natural materials has good cell safety and can avoid human allergies caused by excessive use of chemical additives to a greater extent.

[0024] The present invention also provides the use of the composite nanofiber membrane in preparing skin care mask materials or medical device liquid dressing products.

[0025] The technical effects of the present invention are:

[0026] 1. The composite nanofiber prepared by the present invention is a multi-layer stacked sandwich structure with three-dimensional micro-nano pores, which gives it high air permeability, flexibility and excellent mechanical properties.

[0027] 2. The present invention creatively combines chitosan, hyaluronate and its derivatives with the effective ingredient collagen peptide, so that the functional layer of the nanofiber membrane is no longer just a carrier, but can dissolve by itself and be absorbed by the skin, playing the role of essence, successfully realizing the integration of membrane cloth and essence.

[0028] 3. The nanofiber membrane prepared by the present invention does not contain irritating ingredients such as preservatives, thus solving the problems of chemical additives damaging the skin and causing skin allergies.

[0029] 4. The sandwich structure composite nanofiber membrane cloth of the present invention has good water solubility. After being immersed in water, the fibers swell, but the fiber morphology is still retained. It is not easy to break or deform. It has strong operability and is easy to cut and tailor according to actual needs. It solves the problem that the existing membrane cloth does not fit the skin, and can be used in ordinary skin care mask materials or medical device liquid dressing products.

[0030] 5. The biocompatible material of the present invention can be degraded into harmless components, and is easy to achieve large-scale production, with reduced costs and high yield. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a cross-sectional SEM image of the sandwich structure nanofiber membrane prepared in Example 2;

[0032] Figure 2 : are tensile stress-strain diagrams of fiber membranes of Example 2 and Comparative Examples 1-2, wherein a is the sandwich structure composite membrane of Example 2; b is the functional layer single-layer membrane of Comparative Example 2; and c is the flexible breathable layer and functional layer double-layer membrane of Comparative Example 1;

[0033] Figure 3 These are product performance diagrams of the sandwich structure nanofiber membrane prepared in Example 2, wherein Figure a shows the sandwich structure nanofiber membrane fitting the skin; Figure b shows the appearance of the sandwich structure nanofiber membrane in a after it has been torn off and dried; Figure c shows a sandwich structure composite nanofiber membrane prepared with blue non-woven fabric as the receiving electrode and placed in water; and Figure d is a photograph of the sandwich structure nanofiber membrane in Figure c after it has been taken out and immediately dried with a hair dryer. DETAILED DESCRIPTION

[0034] In order to clearly illustrate the technical features of this solution, this solution is described below through an implementation method.

[0035] Example 1

[0036] 1) Preparation of Adhesion Layer

[0037] Take 0.9g polyvinyl alcohol powder and 0.1g sodium hyaluronate, heat and stir at 90°C, dissolve in 10g and 2g distilled water respectively, add a magnet and place on a magnetic stirrer, stir for 2 hours and then stand, wait for the bubbles to disappear to obtain two spinning solutions. Transfer the spinning solutions to syringes respectively, fix the syringes on the high-voltage electrospinning instrument, set the voltage to 13kV, pattern the receiving device, coaxial electrospinning in the electrospinning mode, the inner layer is sodium hyaluronate, the outer layer is polyvinyl alcohol, set the spinning flow rate to 0.5ml / h, the relative humidity (RH) of the air is 30-40%, the temperature is room temperature, the receiving distance is 7 cm, and the film thickness is 20-30 microns. Control the receiving drum speed to 500r / min, the receiving device is patterned, and the first layer of patterned nanofiber membrane is obtained.

[0038] 2) Functional layer preparation

[0039] The functional layer is composed of chitosan, silanized sodium hyaluronate, and collagen peptide in a mass ratio of 1:1:0.5, which are dissolved in distilled water (the mass percentage of the functional layer to distilled water is 8.5%), and is turned into a uniform solution through magnetic stirring. The solution is placed in a syringe and placed on an electrospinning machine to directly receive the functional layer nanofiber membrane on the surface of the adhesion layer; the electrospinning mode is blended, the relative humidity (RH) of the air is 30-40%, the temperature is room temperature, the propulsion pump is turned on, the spinning flow rate is set to 1.0 ml / h, the high-voltage power supply is turned on, the voltage is adjusted to 15 kV, the receiving distance is 10 cm, and the membrane thickness is 80 microns.

[0040] 3) Preparation of flexible breathable layer

[0041] Weigh 1.2 g of thermoplastic polyurethane powder and place it in a weighing bottle, add 10 ml of N,N-dimethylformamide (DMF) thereto, add a magnet to a magnetic stirrer, stir for 2 hours and wait for the solution to be fully mixed, then remove and let stand until the bubbles in the solution disappear, and directly electrospin a flexible breathable layer on the surface of the functional layer prepared in step 2), with an air relative humidity (RH) of 40% and room temperature. Turn on the propulsion pump, set the spinning flow rate to 1 ml / h, turn on the high-voltage power supply, adjust the voltage to 15 kV, and set the receiving distance to 8 cm. The thickness of the flexible breathable layer membrane is 10 microns.

[0042] Example 2

[0043] 1) Preparation of Adhesion Layer

[0044] Take 0.8g polyvinyl alcohol powder and 0.2g sodium hyaluronate, heat and stir at 85°C and dissolve in 10g and 4g distilled water respectively, add a magnet and place on a magnetic stirrer, stir for 2 hours and then let stand, wait for the bubbles to disappear to obtain two spinning solutions. The receiving device is patterned, the electrospinning mode is coaxial electrospinning, the inner layer is sodium hyaluronate, the outer layer is polyvinyl alcohol, the relative humidity (RH) of the air is 25%, the temperature is room temperature, the receiving distance is 7 cm, and the film thickness is 20 to 30 microns. Control the speed of the receiving drum, the receiving device is patterned, and the other conditions are the same as Example 1 to obtain the first layer of patterned nanofiber membrane.

[0045] 2) Functional layer preparation

[0046] The functional layer is composed of chitosan, sodium hyaluronate and collagen peptide in a mass ratio of 1:1:1. They are dissolved in distilled water (the mass ratio of the functional layer to distilled water is 9%), and are turned into a uniform solution by magnetic stirring. The electrospinning mode is used for blending. The relative humidity (RH) of the air is 30%, the temperature is room temperature, the spinning flow rate is 2.0 ml / hour, the high-voltage power supply voltage is 13 kV, the receiving distance is 10 cm, and the functional layer film thickness is 80 microns obtained by direct electrospinning on the surface of the adhesion layer.

[0047] 3) Preparation of flexible breathable layer

[0048] Same as Example 1.

[0049] The cross-section SEM analysis of the sandwich structure composite nanofiber membrane prepared in Example 2 was performed. Figure 1 As shown, the three layers of nanofiber membranes fit closely together.

[0050] The performance of the sandwich structure nanofiber membrane prepared in Example 2 is as follows Figure 3 As shown, Figure 3 a is a picture of the sandwich structure nanofiber membrane fitting the skin, it can be seen that it has good fit with the skin. Figure 3 b. For a more intuitive display, Figure 3 c provides a picture of a sandwich structure composite nanofiber membrane prepared with a blue nonwoven fabric as a receiving electrode and placed in water; Figure 3 D is Figure 3 c is a photo of the sandwich structure nanofiber membrane after being taken out and immediately blown dry with a hair dryer. Figure 3 It can be fully demonstrated that the sandwich structure composite nanofiber membrane cloth has good water solubility. After being immersed in water, the fibers swell, but the fiber morphology is still retained.

[0051] Example 3

[0052] 1) Preparation of Adhesion Layer

[0053] Take 0.5g polyvinyl alcohol powder, 0.5g sodium hyaluronate, heat and stir at 85°C and dissolve in 5g and 5g distilled water respectively, add a magnet and place on a magnetic stirrer, stir for 2 hours and then let stand, wait for the bubbles to disappear to obtain two spinning solutions. The receiving device is patterned, the electrospinning mode is coaxial electrospinning, the inner layer is sodium hyaluronate, the outer layer is polyvinyl alcohol, the relative humidity (RH) of the air is 25%, the temperature is room temperature, the receiving distance is 7 cm, and the film thickness is 20 to 30 microns. Control the speed of the receiving drum, the receiving device is patterned, and the other conditions are the same as Example 1 to obtain the first layer of patterned nanofiber membrane.

[0054] 2) Functional layer preparation

[0055] The functional layer is composed of chitosan, zinc hyaluronate, and collagen peptide in a mass ratio of 1:1:2. They are dissolved in distilled water (the mass ratio of the functional layer to distilled water is 10.2%), and are turned into a uniform solution by magnetic stirring. The electrospinning mode is blended, the air relative humidity (RH) is 30%, the temperature is room temperature, the spinning flow rate is 2.0 ml / h, the high-voltage power supply voltage is 13 kV, the receiving distance is 10 cm, and the thickness of the functional layer directly electrospun on the surface of the adhesion layer is 80 μm.

[0056] 3) Preparation of flexible breathable layer

[0057] Same as Example 1.

[0058] Comparative Example 1 (double-layer membrane structure)

[0059] 1) Functional layer preparation

[0060] The functional layer is composed of chitosan, sodium hyaluronate and collagen peptide in a mass ratio of 1:1:1. They are dissolved in distilled water (the mass ratio of the functional layer to distilled water is 9%), and are turned into a uniform solution by magnetic stirring. The electrospinning mode is blended, the relative humidity (RH) of the air is 30%, the temperature is room temperature, the spinning flow rate is 2.0 ml / h, the high-voltage power supply voltage is 13 kV, the receiving distance is 10 cm, and the thickness of the functional layer directly electrospun on the surface of the adhesion layer is 80 μm.

[0061] 2) Preparation of flexible breathable layer

[0062] Same as Example 1.

[0063] Comparative Example 2 (single-layer film structure)

[0064] The functional layer is composed of chitosan, sodium hyaluronate and collagen peptide in a mass ratio of 1:1:1. They are dissolved in distilled water (the mass ratio of the functional layer to distilled water is 9%), and are turned into a uniform solution by magnetic stirring. The electrospinning mode is blended, the relative humidity (RH) of the air is 30%, the temperature is room temperature, the spinning flow rate is 2.0 ml / h, the high-voltage power supply voltage is 13 kV, the receiving distance is 10 cm, and the thickness of the functional layer directly electrospun on the surface of the adhesion layer is 80 μm.

[0065] It must be pointed out that the relative thickness of the above-mentioned layers of film can be changed according to actual conditions.

[0066] Test Example 1: Tensile Test

[0067] The nanofiber membranes obtained in Example 2 and Comparative Examples 1-2 were subjected to tensile tests. Tensile test: After drying in an oven at 45°C for 10 hours, the fiber membranes were cut into sample strips with a width of 15 mm and a length of 30 mm for standby use. 20 points of each sample membrane were taken, and the thickness was measured with a micrometer, and the average value was taken. The tensile fracture of the fiber membrane was studied using an LLY-06E electronic single fiber strength tester (Laizhou Electronic Instrument Co., Ltd.).

[0068] Depend on Figure 2 It can be seen from the tensile stress-strain curve of the fiber membrane that the stretchability obtained in Example 2 can reach 112.05% ( Figure 2 a), significantly higher than the stretchability of the functional layer single-layer film (Comparative Example 2) 48.47% ( Figure 2 b) and a flexible breathable layer and a functional layer double-layer film (Comparative Example 1) with a stretchability of 56.95% ( Figure 2 c), it can be seen that the tensile properties of the sandwich structure composite nanofiber membrane are significantly improved.

[0069] Test Example 2: Verification of the Moisture Retention of the Sandwich Structure Composite Nanofiber Membrane Prepared in Example 2

[0070] 30 patients with transepidermal water loss TEWL ≥ 20 g / m were selected 2 h volunteers completed the test, and no volunteers dropped out during the test period. The test was conducted using the skin water loss tester Aqua Flux.

[0071] Results: The test results of the TEWL values ​​of the samples before use, after 2 weeks and after 4 weeks of use are shown in Table 1. The smaller the TEWL value, the slower the TEWL value. From the results in Table 1, it can be seen that the sandwich structure composite nanofiber membrane prepared in Example 2 has good moisturizing properties. After 4 weeks of use, the TEWL value of the TEWL value of the TEWL value is reduced by only 8.35%.

[0072] Table 1 Descriptive statistics of transepidermal water loss TEWL values ​​(n=30)

[0073] Data Types Before use After 2 weeks of use After 4 weeks of use <![CDATA[Average value (g / m 2 h)]]> 24.44 23.53 22.40 <![CDATA[Standard deviation (g / m 2 h)]]> 3.61 4.07 4.32 The relative change rate of the initial value / -3.72% -8.35%

[0074] Test Example 3: Irritation Test

[0075] Human skin patch test was conducted in accordance with the Cosmetic Safety Technical Specifications 2015.

[0076] Experimental group: the sandwich structure composite nanofiber membrane prepared in Example 2;

[0077] Control group: commercially available facial mask (basic information: milky white translucent liquid attached to non-woven membrane cloth, core ingredient: hyaluronic acid, main effect: moisturizing, repairing the barrier to resist external stimuli);

[0078] Subjects: A total of 30 people, 0 males and 30 females, aged 23-50 years old, met the voluntary selection criteria for subjects.

[0079] Test method: Select an area not exceeding 50mm 2 , depth of about 1mm. Apply the test substance to the test device using the closed patch test method. Apply the test device to the flexor side of the subject's forearm. Remove the test substance after 24 hours and record the skin reaction 0.5 and 24 hours after removal. Record the results according to the skin reaction grading standard in the "Cosmetic Safety Technical Specifications 2015". The skin reaction grading standard is shown in Table 2.

[0080] Table 2 Skin reaction grading standards

[0081]

[0082] Table 3 Results of cosmetic human skin patch test

[0083]

[0084] Test results: The results are shown in Table 3. In the experimental group, no adverse skin reactions occurred in the 30 subjects at 0.5 hours and 24 hours after removal. In the control group, 2 subjects had grade 2 skin reactions at 0.5 hours after removal, and 28 subjects had no adverse skin reactions; at 24 hours after removal, no adverse skin reactions occurred in the 30 subjects.

[0085] The above-listed embodiments are only for understanding the present invention and are not intended to limit the technical solutions described in the present invention. A person skilled in the art may make various changes or modifications based on the technical solutions described in the claims, and all equivalent changes or modifications shall be included in the protection scope of the claims of the present invention. Anything not described in detail in the present invention is a known technology to those skilled in the art.

Claims

1. An electrospun composite nanofiber membrane, characterized in that: It is a sandwich structure composite nanofiber membrane consisting of an adhesive layer, a functional layer and a flexible breathable layer; The adhesive layer is a biocompatible electrospun polyvinyl alcohol / sodium hyaluronate nanofiber membrane, the electrospinning mode of which is coaxial electrospinning, the inner layer is sodium hyaluronate, and the outer layer is polyvinyl alcohol; the mass ratio of polyvinyl alcohol to sodium hyaluronate is 90:10-50:50; The functional layer is a nanofiber membrane comprising chitosan, hyaluronate and its derivatives, and collagen peptide; the mass ratio of chitosan, hyaluronate and its derivatives, and collagen peptide is 1:0.8-1.2:0.5-2; The flexible breathable layer is an ultra-thin thermoplastic polyurethane nanofiber membrane.

2. The electrospun composite nanofiber membrane according to claim 1, characterized in that: The thickness of the adhesive layer is 20-30 μm; the thickness of the functional layer is 60-80 μm; and the thickness of the flexible breathable layer is 8-12 μm.

3. The method for preparing the electrospun composite nanofiber membrane according to claim 1 or 2, characterized in that: The following steps are involved: 1) Preparation of Adhesion Layer Take polyvinyl alcohol and sodium hyaluronate, add water, heat and stir respectively, to obtain two spinning solutions; transfer the spinning solutions into syringes respectively, fix the syringes on a high-voltage electrospinning instrument, set the receiving device to pattern, and electrospin the electrospinning mode to coaxially electrospin, with the inner layer being sodium hyaluronate and the outer layer being polyvinyl alcohol, and electrospinning to obtain the first layer of patterned nanofiber membrane; 2) Preparation of functional layer Dissolving chitosan, hyaluronate and its derivatives, and collagen peptide in water to form a spinning solution, and mixing them in an electrospinning mode to directly receive the functional layer nanofiber membrane on the adhesive layer prepared in step 1); 3) Preparation of flexible breathable layer Thermoplastic polyurethane is dissolved in N,N-dimethylformamide solvent to obtain a spinning solution, and the flexible air-permeable layer nanofiber membrane is directly received on the functional layer in step 2).

4. The method for preparing the electrospun composite nanofiber membrane according to claim 3, characterized in that: In step 1), the concentrations of the polyvinyl alcohol and sodium hyaluronate spinning solutions are 8-10 wt % and 5-10 wt %, respectively.

5. The method for preparing the electrospun composite nanofiber membrane according to claim 3, characterized in that: In the spinning process of step 1), the relative humidity of the air is 25-40%, the temperature is room temperature, and the receiving distance is 7 cm.

6. The method for preparing the electrospun composite nanofiber membrane according to claim 3, characterized in that: In the step 2), the total mass percentage of the functional layer chitosan, hyaluronate and its derivatives, and collagen peptide to the mass percentage of distilled water is 8-12%.

7. The method for preparing the electrospun composite nanofiber membrane according to claim 3, characterized in that: In the spinning process of step 2), the relative humidity of the air is 30-40%, the temperature is room temperature, and the receiving distance is 10 cm.

8. The method for preparing the electrospun composite nanofiber membrane according to claim 3, characterized in that: In step 3), the concentration of the thermoplastic polyurethane spinning solution is 0.1-0.15 g / ml.

9. The method for preparing the electrospun composite nanofiber membrane according to claim 3, characterized in that: In the spinning process of step 3), the relative humidity of the air is 30-40%, the temperature is room temperature, and the receiving distance is 8 cm.

10. Use of the electrospun composite nanofiber membrane according to claim 1 or 2 in the preparation of skin care mask membrane materials or medical device liquid dressing products.

Citation Information

Patent Citations

  • Composite fiber facial mask rich in collagen and preparation method thereof

    CN107374983A

  • Preparation method of moisturizing and hydrating nanofiber mask

    CN112587443A

  • Preparation method of composite nanofiber membrane for wound dressing and composite nanofiber membrane

    CN114949325A